Opportunities for strategic decision making in managing ex situ germplasm collections - Hanson, Jean; Lusty, C.; Furman, B.J.; Ellis, D.; Payne, T.; Halewood, M. (Cambridge University Press, 2024)
Efficient conservation and sustainable use of crop diversity is critical to support global food and nutritional security with ex situ collections stored in over 800 genebanks in 115 countries. The challenge is to manage those collections for long-term conservation of crop diversity and sustainable use to respond to global challenges of food security and climate change. The Genebank Standards for Plant Genetic Resources for Food and Agricutlure (Genebank Standards) form the overall framework for curation of ex situ crop collections, allowing considerable flexibility to develop customized approaches to conserving different crops. Stratified curation involves strategically tailoring curation to specific genebank goals, crops, priorities and resources for each accession based on all available information to prioritize accessions for long-term conservation. It implies using scarce resources where they are most needed and recognizes that accessions can be (a) fully curated to international standards; (b) partially curated for storage for a limited time; (c) archived and stored but no longer curated and available from the genebank; or (d) historical and removed entirely from the genebank. The stratified approach is consistent with the Genebank Standards and the policy framework of the International Treaty on Plant Genetic Resources for Food and Agriculture. Stratified curation encourages curators to make difficult decisions on accession management to better respond to challenges of curating large collections of crop diversity.